2011
DOI: 10.1111/j.1096-3642.2011.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteology and phylogenetic relationships of Tehuelchesaurus benitezii (Dinosauria, Sauropoda) from the Upper Jurassic of Patagonia

Abstract: The diversification and early evolution of neosauropod dinosaurs is mainly recorded from the Upper Jurassic of North America, Europe, and Africa. Our understanding of this evolutionary stage is far from complete, especially in the Southern Hemisphere. A partial skeleton of a large sauropod from the Upper Jurassic Cañadón Calcáreo Formation of Patagonia was originally described as a 'cetiosaurid' under the name Tehuelchesaurus benitezii. The specimen is here redescribed in detail and the evidence presented indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(135 citation statements)
references
References 62 publications
5
124
3
3
Order By: Relevance
“…Yet other studies have even found Alamosaurus to be a lithostrotian titanosaur outside the clade Saltasauridae (Fig. 14D) (Upchurch 1998;Upchurch et al 2004;Carballido et al 2011;Carballido & Sander 2014;Poropat et al 2015). Other anatomical studies have concluded that Alamosaurus bears greater similarity to South American titanosaurs than to Opisthocoelicaudia (Lehman & Coulson 2002;Fronimos & Lehman 2014).…”
Section: Phylogenetic Analysismentioning
confidence: 93%
“…Yet other studies have even found Alamosaurus to be a lithostrotian titanosaur outside the clade Saltasauridae (Fig. 14D) (Upchurch 1998;Upchurch et al 2004;Carballido et al 2011;Carballido & Sander 2014;Poropat et al 2015). Other anatomical studies have concluded that Alamosaurus bears greater similarity to South American titanosaurs than to Opisthocoelicaudia (Lehman & Coulson 2002;Fronimos & Lehman 2014).…”
Section: Phylogenetic Analysismentioning
confidence: 93%
“…Though they maintained the denomination as "upper section of the Cañadón Asfalto Formation," Figari and Courtade (1993) noted that this Cañadón Calcáreo Formation is equivalent to their megasequence II, in which they also included the "estratos de Almada" (see also Cortiñas, 1996;Page et al, 1999;Figari, 2005). Following this revision, and based on own observations in the field, Rauhut (2003Rauhut ( , 2006aRauhut ( , 2006b, López-Arbarello (2004), Rauhut et al (2005), López-Arbarello et al (2008), andCarballido et al (2011) referred to this unit as Cañadón Calcáreo Formation, including the "estratos de Almada" (Figure 1). Although Volkheimer et al (2008Volkheimer et al ( , 2009) accepted the referral of the "estratos de Almada" to the Cañadón Calcáreo Formation, assigning an Early Cretaceous (Valanginian) age FIGURE 2.…”
Section: Geological Settingsmentioning
confidence: 99%
“…Apart from the Almada fish fauna, vertebrate remains from other parts of the Cañadón Calcáreo Formation include a new species of crocodile from the fluvial beds above the fish layers at Puesto Almada , the sauropod dinosaurs Tehuelchesaurus (Rich et al, 1999;Carballido et al, 2011), Brachytrachelopan (Rauhut et al, 2005) and an undeterminate brachiosaurid (Rauhut, 2006a), as well as undescribed remains of theropod dinosaurs and temnospondyl amphibians (OWMR pers. obs.).…”
Section: Geological Settingsmentioning
confidence: 99%
“…D'Emic claimed that dorsal vertebrae illustrated by Osborn and Mook (1921:plates LXIX and LXXII) have forward-sloping neural arches resembling those of Xenoposeidon: in reality, only one posterior dorsal vertebrae out of four complete dorsal columns illustrated in that monograph shows a forward slope, and it differs so much from its fellows that this can only be interpreted as the result of crushing. D'Emic further claimed that the lamina patterns observed in Xenoposeidon can be recognised in other sauropods, but I have been unable find morphology resembling them in the descriptions he suggests: Osborn and Mook 1921 for Camarasaurus, Riggs 1903 for Bracdiosaurus (probably a typo for Riggs 1904, which also does not depict similar patterns), Carballido et al 2011 for Teduelcdesaurus. A similar pattern does appear in Rebbacdisaurus, as will be discussed below.…”
Section: Introductionmentioning
confidence: 99%